An Analysis of Theories in Biomechanics - Prendergast, P.J. (Engineering Transactions, 2001)
The nature of the systems commonly thought of as coming into the remit of biomechanics range from 'mechanical' systems (concerned with the design of medical devices, such as implants) to 'mechanobiological' systems (concerned with the response of tissues, cells, and biomolecules to mechanical forces). In each case, a biomechanical system is characterised by the interaction of biological and physical elements. Like any other science, biomechanics advances by the development of theories and the testing of these theories by observation and experiment. The purpose of this paper is to analyse contemporary biomechanics research by providing a critique of the development of biomechanical theories. Only two are considered in detail: (i) the theory of hip prosthesis failure and (ii) the theory of adaptive-bone remodelling. In both cases, specific basic statements, or hypotheses, have been proposed and tested using computational and experimental methods. In the case of hip implants, there have been definite advances in the sense that many hypotheses that could have been rejected continue to be upheld despite severe testing. On the other hand, in the case of adaptive-bone remodelling where the dominant theory is 'adaptive elasticity', the tests of the theory have either been too lenient or they have smuggled in new assumptions that fundamentally alter it. The problems of testing adaptive-elasticity theory are described, and comparison is made with damage-based bone remodelling theories.